2020
DOI: 10.1002/adfm.202004650
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional 3D Hierarchical Hairy Foam toward Ultrastable Lithium/Sulfur Electrochemistry

Abstract: The dendrite formation resulting from the irregular lithium deposition and the infinite volume expansion in lithium anodes significantly impede their commercialization for high energy applications. Herein, it is demonstrated that carbon nanofibers (CNFs) grown in situ on a nickel foam (CNF@Ni) can locally change the Li stripping/plating behavior by reducing the nucleation overpotential and regulating the electric field distribution. The 3D conductive hairy foam with a hierarchical structure can provide suffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…Recently, academia’s awareness of devising Li–S full cells has been gradually raised. Research interests are mainly focused on the design of electrode frameworks (e.g., catalyst-modified carbon fabrics and lithiophilic 3D metal skeletons ), but the introduction of porous hosts will intensify the compromise of E v . More importantly, the N/P ratio is rarely explicitly controlled, which does not satisfy the eligibility criteria of Li–S full cells.…”
Section: Transition Of Electrochemical Behaviormentioning
confidence: 99%
“…Recently, academia’s awareness of devising Li–S full cells has been gradually raised. Research interests are mainly focused on the design of electrode frameworks (e.g., catalyst-modified carbon fabrics and lithiophilic 3D metal skeletons ), but the introduction of porous hosts will intensify the compromise of E v . More importantly, the N/P ratio is rarely explicitly controlled, which does not satisfy the eligibility criteria of Li–S full cells.…”
Section: Transition Of Electrochemical Behaviormentioning
confidence: 99%
“…It is noteworthy that such remarkable cycling performances are superior to those of previously reported LMAs based on 3D frameworks (Figure 5d ; Table S1 , Supporting Information). [ 28 , 34 , 36 , 37 , 51 , 52 , 53 , 54 , 55 ] To investigate the cycling performance of the Li/CoSe 2 –C@CFC anode under a higher capacity, the executed capacity was further enhanced to 20 mAh cm –2 . As shown in Figure 5e , at a current density of 5 mA cm –2 , the symmetric Li/CoSe 2 –NC@CFC cell exhibited a stable voltage platform that remained for over 1600 h. Moreover, the symmetric cell of the Li/CoSe 2 –NC@CFC can be cycled for over 280 h at 10 mA cm –2 (Figure 5f ), representing its superiority as a high‐energy‐density LMA.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, the use of three‐dimentional (3D) conductive frameworks to accommodate Li plating/stripping has achieved remarkable results. [ 26 , 27 , 28 ] Owing to their light mass, high conductivity, predominant flexibility, and robust structure, carbon‐based frameworks are promising high‐energy‐density Li hosts among numerous frameworks, as well as in the area of flexible energy storage. [ 29 , 30 ] The introduction of lithiophilic materials into carbon‐based frameworks is a representative strategy for promoting Li storage performance.…”
Section: Introductionmentioning
confidence: 99%
“…[43] The long-term cycling performances at high current densities and under a large areal capacity are proved to be essential for practical Li anodes applied to high-energy-density and highpower-density LSBs. [44] Its reported that the nucleation process of Li is heavily dependent on the current density, where the high current density causes serious deterioration of lithium dendrite, which is difficult to meet the demand of rapid charging/discharging in practical application. [42] In Figure 3e, when the current density increases to 3 mA cm −2 , the Li@MCG-2@Cu based symmetric cell still delivers outstanding stability of Li stripping/plating electrochemistry and low voltage hysteresis (nearly 17.9 mV for 760 h), demonstrating the tremendous potential for stable circulation under large current.…”
Section: Lithium Dendrite Suppression Of Mcg-2mentioning
confidence: 99%